Synthesis and Characterization of Terpolymer - Sangu, V.; Srinivasan, K.; Kanaan, K. (Asian Journal of Chemistry, 2010)
para-Hydroxy benzoic acid, thiourea and para-formaldehyde terpolymer resin was synthesized with different molar ratio of monomers in presence of the catalyst 2 M H2SO4 and 2 M HCl. The resin was characterized by IR and UV spectral analysis. Molecular weight of the terpolymer was determination using gel permeation chromatography and thermal stability of the terpolymer was determined by thermogravimetric analysis.